LONTAR FIBER AS ECO-FRIENDLY BUILDING MATERIAL: PUBLIC PERCEPTIONS IN EAST NUSA TENGGARA, INDONESIA - Wella, Yudith Arunika Cempaka; Larasati , Dewi; Tambunan, Lily (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2026)
As environmental issues become more pressing and the world works to reduce carbon emissions, the construction industry is shifting towards using more eco-friendly materials. In East Nusa Tenggara, Indonesia, lontar fiber (Borassus flabellifer) is a widely available, renewable resource that is good for the environment. It can be used to build walls in homes, but its use is still limited. People are not aware of it, there are no clear performance standards, and the public’s opinion of it is not well understood. Aims: This research aims to examine how people perceive and accept lontar fiber as a building material. Methodology and results: The study uses a grounded theory method, which means it closely examines people's views. Data were collected through online questionnaires from 120 carefully selected individuals. The findings show that many people are interested in using lontar fiber because it is eco-friendly, affordable, and easily accessible locally. However, concerns remain about its durability, strength, and reliability. Participants emphasized the importance of testing, education, and small-scale projects to build confidence in the material. Conclusion, significance and impact study: The study shows that lontar fiber could be an excellent, low-carbon building material made from local resources. The study also points out that to use it more widely, a mix of new technology, traditional knowledge, government support, and community involvement is needed to help build a more sustainable future in Indonesia.